MiR-219-5p targets TBXT and inhibits breast cancer cell EMT and cell migration and invasion. Issue 8 (27th August 2021) - Ye, Qin; Wang, Xing; Yuan, Mei; Cui, Shuaishuai; Chen, Yuanyuan; Hu, Zhaodi; Liu, Dandan; Han, Conghui; Li, Bibo; Chen, Dahu
Abstract: miR-219-5p has been reported to act as either a tumor suppressor or a tumor promoter in different cancers by targeting different genes. In the present study, we demonstrated that miR-219-5p negatively regulated the expression of TBXT, a known epithelial–mesenchymal transition (EMT) inducer, by directly binding to TBXT 3′-untranslated region. As a result of its inhibition on TBXT expression, miR-219-5p suppressed EMT and cell migration and invasion in breast cancer cells. The re-introduction of TBXT in miR-219-5p overexpressing cells decreased the inhibitory effects of miR-219 on EMT and cell migration and invasion. Moreover, miR-219-5p decreased breast cancer stem cell (CSC) marker genes expression and reduced the mammosphere forming capability of cells. Overall, our study highlighted that TBXT is a novel target of miR-219-5p. By suppressing TBXT, miR-219-5p plays an important role in EMT and cell migration and invasion of breast cancer cells.